2021
DOI: 10.1186/s12888-021-03458-x
|View full text |Cite|
|
Sign up to set email alerts
|

Recognizing obsessive-compulsive disorder: how suitable is the German Zohar-Fineberg obsessive-compulsive screen?

Abstract: Background Despite the prevalence of obsessive-compulsive disorder (OCD), its precise identification remains challenging. With the Zohar-Fineberg Obsessive-Compulsive Screen (ZF-OCS; 5 or 6 items), a brief instrument is widely available mainly in English. As there is a lack of empirical studies on the ZF-OCS, the aim of the present study was to translate the items into German and investigate the instrument in a nonclinical sample. Methods In two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Following the publication of the original article [ 1 ], the authors identified that the funding note was incorrect. The correct funding note is given below.…”
mentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], the authors identified that the funding note was incorrect. The correct funding note is given below.…”
mentioning
confidence: 99%